Improvement Strategy For Outpatient Medical Record Return Delay At Jambesari Public Health Center Bondowoso - Nuraini, Novita; Kiromah, Siska Ainul; Wijayanti, Rossalina Adi (P3M Politeknik Negeri Jember, 2025)
The delay in returning medical records significantly affects the quality of healthcare services. It was found that at Jambesari Health Center, there is a delay in returning outpatient medical records by 80 % due to the absence of Standard Operating Procedures (SOP), lack of tracer usage, and limited information media about service hours. Therefore, the purpose of this study is to develop an improvement strategy for outpatient medical record return delay using the PDCA approach. This type of research uses qualitative. The research informan were 8 informants consisting of 6 main subjects, namely 1 medical records officer, 1 counter clerk, 1 nurse, 1 general practitioner, 1 midwife, 1 dentist and 2 supporting subjects, namely 1 head of community health center and 1 head of administration. Data collection method use interviews, observation, documentation and brainstorming. The planning phase resulted in identifying 3 priority causes from the 7M process elements, namely the absence of specific SOP for returning outpatient medical records, lack of tracer usage and insufficient information for the community regarding operating hours with improvement actions including creating SOPs related to outpatient medical record return, acquiring tracers, and using banners as information media for service hours. The implementation phase lasted for 3 months from March to May 2023, guided by previously established TOR. The checking phase revealed a decrease of record return delay by 17% after improvements, followed by the action phase, which included brainstorming and socializing SOPs every month and optimizing tracer design and medical record training.